Development of Surface Roughness Prediction Model using Response Surface Methodology for End Milling of HTCS-150 - Hadzley, A.B.; Azahar, W.M.; Anis, A.A.; Izamshah, R.; Amran, M.; Kasim, S.; Noorazizi, S. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
In the present study, a regression mathematical model has been developed to predict the surface roughness in end milling of High Thermal Conductivity Steel 150 (HTCS-150). A number of milling experiments were conducted using the Response Surface Methodology (RSM) approach using CNC variaxis machining centre. The cutting speeds (484-553 m/min), feed rates (0.31-0.36 mm/tooth) and depth of cut (0.1-0.5 mm) were selected as the control factors. Analysis of variance (ANOVA) was used to analyze the most significant control factors affecting the surface roughness. Box-behnken experimental design was employed to create a mathematical model. The results show that the mathematical modeling developed in this study able to predict the output values of the surface roughness for milling HTCS-150. Cutting speed appeared to be the most influencing parameter for fine surface roughness, followed by depth of cut and feed rate. The differences between measured and calculated values stated about 4 % error.